Influência do espaçamento das armaduras de cisalhamento na resistência à punção de lajes lisas com estribos treliçados pré-fabricados - COSTA, Denilda Silva (Universidade Federal do Pará, 2024)
The shear check on the slab-column connection of flat slabs in reinforced concrete is the critical point of design in the ultimate limit state. Punching failure is the critical point in the design of flat slabs and is defined as a sudden and fragile failure due to shears in the region of connection between the slab and the column, the best option for the control of failure by flat slabs is to use of shear reinforcement. National and international regulations such as the use of shear reinforcements that involve bending reinforcements in a way that their anchoring is guaranteed. However, this model makes the executive process difficult, requiring configurations between the bending and shear protections at the construction site. This research aims to present a technical and constructive solution to the problem of shear resistance in flat slabs in the slab-column connection through the use of shear reinforcement proposed by Ferreira et al. (2016), prefabricated truss stirrups, varying the values of the shear reinforcement rates and the spacing between the reinforcement layers. Positioned between the upper and lower flexural reinforcements, it has speed in execution and the possibility of manpower, as it is industrially bent and positioned on the job site, the useful height of the slab and the economy eliminates conflicts between the shear and flexural reinforcements. To compare the results and analyze the performance, tests were carried out on 5 flat reinforced concrete slabs, one of the slabs was reinforced with a flexural reinforcement rate ρ 2,0%, and the others with ρ1%, the reinforcement rate of shear (ρw) varies from 0.49% to 0.99%. As the instrumented in a way that could be the non-designed displacement forms, as in the flexural, shear and complementary reinforcements. The slabs were instrumented so that the vertical displacements, the deformations in the concrete and in the flexural, shear and complementary reinforcements could be obtained. The slabs were dimensioned so that the failure occurred by punching within the region of the shear reinforcement following the normative calculation recommendations of NBR 6118 (ABNT, 2014), ACI 318 (2019), Eurocode2 (2014), fib Model Code 2010 (2013) and the EOTA technical report (2017). From the analysis of the results, it was concluded that all slabs failed by punching, the slabs reinforced with prefabricated truss stirrups showed a strength gain of 73% for the SW3 slab when compared to the reference slab (S0) from Freitas (2018) and of 55%, 58%, 45% and 50% for slabs SW4, SW5, SW6 and SW7, respectively, when compared with the predictions of NBR 6118 (ABNT, 2014), slabs with reinforcement positioned up to 1.125d from the column face showed higher strength increase values and ultimate strength values similar to those of slabs with constant spacing, even with reduction of the total amount of steel by up to 95,2% of its weight.